The emerging contours of a post-Brexit Britain. (25th January 2022) - Adam, Christopher
Abstract: This paper introduces a set of papers analysing the likely economic impact of Brexit across key aspects of the UK economy as the country comes to the end of its first full year outside the European Union. The Brexit vote in 2016 was not just a vote on the UK's relations with the institutions of the European Union but was also a referendum on the fractured state of the UK as a nation. The resulting conflation of Brexit with domestic economic policy debates is reflected in this issue. A first cluster of papers focuses on the consequences of choosing to abandon the 'four freedoms' enshrined in the Treaty of Europe, the free movement of goods, services, capital, and labour across the EU, and a second is concerned with the indirect effects of Brexit in those areas of domestic policy that have been opened up by the Brexit decision. The economic consequences of Brexit are only just emerging, but these papers provide an informed perspective on the state of debate, and the likely implications of Brexit across a range of policy areas, both international and domestic.